2010
DOI: 10.1021/jp107916c
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and Isomerism in SFn−1Cl (n = 1−6): A Quantum Chemical Study

Abstract: Using high-level MRCI and CCSD(T) quantum chemical calculations, we report structures, energetics, and other properties of the sulfur fluoromonochloride family (SF(n-1)Cl, n = 1-6). Our group previously studied the sulfur fluoride family (SF(n), n = 1-6) and found that several of the excited states of SF and SF(2) as well as the ground states of SF(3)-SF(6) exhibited a new type of bonding, called recoupled pair bonding. Comparing the SF(n-1)Cl and SF(n) species allows us to study isomerism, apicophilicities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 59 publications
9
57
0
Order By: Relevance
“…The bond pair in the SF 2 (a 3 B 1 ) state is clearly a recoupled pair bond dyad and dyads derived from p lone pairs tend to favor nearly linear configurations. [3][4][5][6][7] In line with previous studies, 3 we find that the second bond in SF 2 (a 3 B 1 )-the polar covalent bond-is very strong, 106.32 kcal/mol, over 15 kcal/mol stronger than the second bond in the ground state of SF 2 . This increase in bond strength results from the decrease in the overlap between the unpaired, singly occupied σ orbital of SF and the SF bond pair in the F A S fragment as the F A S-F B distance decreases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The bond pair in the SF 2 (a 3 B 1 ) state is clearly a recoupled pair bond dyad and dyads derived from p lone pairs tend to favor nearly linear configurations. [3][4][5][6][7] In line with previous studies, 3 we find that the second bond in SF 2 (a 3 B 1 )-the polar covalent bond-is very strong, 106.32 kcal/mol, over 15 kcal/mol stronger than the second bond in the ground state of SF 2 . This increase in bond strength results from the decrease in the overlap between the unpaired, singly occupied σ orbital of SF and the SF bond pair in the F A S fragment as the F A S-F B distance decreases.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, [3][4][5][6][7] we found that, for the late p-block elements, formation of a second central atom-ligand bond involving the electron in the unpaired, singly occupied orbital left over from the formation of the recoupled pair bond results in a bond that is far stronger than the recoupled pair bond. Its strength can even be larger than the corresponding central a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 82%
“…As has been shown by Dunning and coworkers, the structures and energetics of all of the hypervalent molecules that they studied-SFn, 137 SFn-1Cl, 143 SCln, 144 PFn, 145 PFn-1Cl, 146 H(SO), 147 S2F4, 148,149 SO2, 150,151 ClnSO, 152 ClFn, 153 ClFn + , 154 and ClFn -155 -follow the pattern observed above for SFn (see also Refs. 156, 157, and 158).…”
supporting
confidence: 76%
“…5 Previous studies of the halides of the second row, late p-block elements, by our group have shown that hypervalent or hypercoordinated molecules possess a previously unrecognized type of bond, a recoupled pair bond. [6][7][8][9][10][11][12][13][14] Recoupled pair bonds and recoupled pair bond dyads 14 the stability of SF 4 and SF 6 , 7 as well as other hypervalent species such as PF 5 , 9 ClF 3 , and ClF 5 , 8 providing a simple, straightforward explanation of the low-lying states, structures, and energetics of these species as well as those of the intermediate SF n , PF n , and ClF n radicals. In fact, it has been found that the ability of elements beyond the first row to form recoupled pair bonds accounts for a number of the differences between the structures, energetics, and spectra of compounds of the first and second row elements, including differences in reactivity 13 -the so-called first-row anomaly.…”
Section: Introductionmentioning
confidence: 99%